Dean Peeters, Shaping Regionality in Socioeconomic Systems: Late Hellenistic – Late Roman Ceramic Production, Circulation, and Consumption in Boeotia, Central Greece (c. 150 BC-AD 700). Roman and Late Antique Mediterranean Pottery 18. - Lund, John (Journal of Greek Archaeology, 2025)
The publication of Dean Peeters’ ambitious monograph is timely, seeing that regions and ‘micro-regions’ in antiquity are attracting increasing scholarly interest. It is based on the author’s recent Ph.D. thesis from the University of Cologne, and he explains in the introduction that its aim is ‘to highlight and explain the shaping of socioeconomic diversity in Boeotia (Central Greece) from c. 150 BC to AD 700’, defining two central research questions: 1) How did local and regional economies look, work from within, and link into larger socioeconomic networks and systems? And 2) How were differences in the workings and development of economies and communities shaped in space and time? To come up with answers, Peeters looks to new data provided by archaeology, and in particular to pottery studies, which are in his view capable of throwing ‘interesting lights on locally-anchored and socially-embedded economies, socioeconomic networks, and agency by extension’. This is the central premise of the volume, which builds on the author’s meticulous evaluation of ceramic evidence from the Boeotia Project, which is – somewhat curiously – only introduced to the reader later.